Las humanidades: el alma de las sociedades: The Humanities: The soul of Societies - Navarro Jiménez, Karina (Universidad del Zulia, 2021)
This text constituted the pronouncement of the School of Philosophy of the University of Zulia, in response to the document emanating from the Ministry of University Education of Venezuela called: "Re-dimensioning of the National System of University Admission, Based on the Reactivation of the Productive Apparatus" given to know in December 2020. This official document expresses the government's will to prioritize university careers considered extremely important, given the current socio-economic circumstances in Venezuela. However, we think that humanistic careers are not taken into account under any consideration and we interpret that such omission within the indicated document harms the future of the various careers of this nature.